Thirty-Day Unplanned Readmission after Total Hip Arthroplasty at a Community Hospital: Rates, Reasons, and Risk Factors - Workman, Kalain; Folau, Christopher K.; Phillips, David S. (The Journal of Hip Surgery, 2021)
Unplanned readmission after total hip arthroplasty (THA) has an increasing prevalence in the United States. Readmissions are a metric for a hospital's quality of care, yet the reasons behind them are mixed. In this changing health-care environment, it is critical for institutions to identify the risk factors for unplanned readmissions following a THA. Retrospective chart review and hospital administrative database query were used to report causes, demographics, and medical comorbidities linked to a 30-day readmission after primary THA at a teaching community hospital system. This study identified 4,459 primary THA procedures, of which 96 (2.2%) were unplanned readmissions. Periprosthetic fracture (20.8%) and periprosthetic infection (17.7%) were the most common causes of readmission. Patients discharged to rehab (odds ratio [OR], 2.44; 95% confidence interval [CI], 1.36–4.37; p = 0.0026) were correlated significantly with the risk of 30-day readmission. Anemia (OR, 2.62; 95% CI, 1.44–4.79; p = 0.0016), obstructive sleep apnea (OR, 2.27; 95% CI, 1.17–4.4; p = 0.0150), and asthma (OR, 2.51; 95% CI, 1.17–5.40; p = 0.0184) were significant independent risk factors. Charlson comorbidity index (p = 0.3634) was not shown to correlate with a quicker readmission within 30 days of discharge. Patients with a history of anemia, obstructive sleep apnea, and asthma should be medically optimized before and after undergoing THA in the community setting. Implementing postsurgical emphasis on discharging patients with home care options rather than transferring them to a rehabilitation facility may prevent 30-day readmissions.
Keywords: adult reconstruction; total hip arthroplasty; readmissions; medical comorbidities